Dyspnea in Cancer Patients: A Well-Known and Neglected Symptom - Meriggi, Fausto (Reviews on Recent Clinical Trials, 2018)
Background: Dyspnea is a very common and well-known symptom in patients with advanced cancer, but it is often neglected by physicians. Moreover, despite the high frequency of dyspnea, few controlled studies have been conducted on cancer patients. In most cases, this ‘awareness of breathing with difficulty’ and its severity can only be judged by the patient. Moderate or severe dyspnea is described in 20-80% of patients with advanced cancer and breathlessness is considered a prognostic factor for shorter survival, either alone or associated with other parameters. Methods: I reviewed the literature and guidelines on the topic with the aims to focus on what is known and on future pathways to follow for the diagnosis and treatment of dyspnea. Results: There is no uniformity regarding the definition of dyspnea; consequently, there is still no general agreement about which tools are the best to use in clinical practice to detect the presence and severity of this symptom. In addition to the difficulty of assessing the symptom, a further limit concerns the management of dyspnea: a very limited number of therapies, both pharmacological and otherwise, are currently available that lead to satisfactory outcomes. Opioids such as morphine remain the cornerstone of treating dyspnea. Conclusion: Dyspnea is a complex, multidimensional symptom that results from an interaction between factors and their causes, perception and expression. The main target of assessment and management is the intensity of dyspnea, as expressed by the patient, rather than the objective parameters of the disease. Although dyspnea is a very common symptom, debilitating and often difficult to control, especially in the terminal phase of the disease, few controlled studies have been conducted on cancer patients. Dyspnea remains a well-known but neglected symptom in advanced and terminal cancer patients. Future studies should be conducted regarding the careful assessment and management of this symptom.
Keywords: Advanced cancer